CLINICAL-PSYCHOPATHOLOGICAL AND PSYCHODIAGNOSTIC CHARACTERISTICS OF PATIENTS WITH PARANOID SCHIZOPHRENIA AND ITS DIAGNOSTIC VALUE - Юрченко, О.М. (World of Medicine and Biology, 2016)
The aim of this work is to evaluate the diagnostic value of clinical-psychopathological and psychodiagnostic characteristics of patients with paranoind schizophrenia (PS) and possibilities of their use to increase the reliability of recognition of the mental disorder using modern methods of complex account of disparate symptoms.Contingent and methodsThe Symptom Checklist-90-Revised (SCL-90-R) by Derogatis was used in this work. 107 patients with PS and 70 healthy volunteers (all surveyed were male), of comparable age (36,45 ± 0,91 years and 36, 53 ± 1.74 years, respectively) were examined.For all studied signs diagnostic coefficients (DC) and measures of informativity (MI, by Kullback) were calculated.Results It was found that the average severity of psychopathology in patients with PS at almost all scales was expectedly and significantly (p 0.6 points (DC = 11.02; MI = 2.75); obsessive-compulsive > 1.00 points (DC = 14.28; MI = 2.63); and psychoticism > 0.3 points (DC = 10.79; MI = 2.54).
Keywords: paranoid schizophrenia; complex diagnostics; indirect signs; consecutive Wald procedure